Technological Indicators of New Structure Two-Layer Knitted Fabrics Analyzed (Eurasian Journal of Engineering and Technology, 2023)
In the article technological capabilities of modern double bed flat knitting machines results of analyses of technological parameters double-layer knitted fabrics